Dinamika Hukum Ekonomi Syariah di Indonesia: Telaah Politik Hukum - Santoso, Lukman (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2022)
Legislation as a political product is ideally a representation of the people's aspirations and, at the same time, can impact the benefit of the people at large. However, in practice, the dominance of the interests of the political elite makes the resulting legal products represent political interest groups. This article explores the dynamics of Sharia economic law after reform in Indonesia. This research uses a conceptual-juridical approach and is a type of qualitative research. Data collection techniques are carried out by digging library sources relevant to the study topic. This study finds that the internal socio-cultural dynamics of Muslims largely determine the dynamics of Sharia economic law in post-reform Indonesia on the one hand, Islamic-leaning political parties in parliament, as well as fluctuations in the relationship between Muslims and the state. A conducive political climate enables the development of the Islamic financial industry in the region and nationally. This dynamic contributes to strengthening Sharia economic values ​​in the legislative process and bureaucratization of Sharia economic law in the national legal ecosystem.